2007
DOI: 10.1177/000348940711600106
|View full text |Cite
|
Sign up to set email alerts
|

Somatic Modulation of Tinnitus: Test Reliability and Results after Repetitive Muscle Contraction Training

Abstract: Maneuvers of head and neck muscle contractions evoked tinnitus modulation in a frequent and reliable manner. Also, the repetition of such maneuvers for 2 months altered the pattern of modulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
71
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(79 citation statements)
references
References 13 publications
7
71
0
1
Order By: Relevance
“…The identification of a somatic origin for her tinnitus thanks to the matching of self-reported history and modulation in the same somatic regions helped in addressing this patient to multidisciplinary somatic evaluation and treatment. Furthermore, the characteristics of tinnitus modulation found in this patient are consistent with what reported in the literature by some authors 32,33,41,42 . TMJ maneuvers induced an increase in tinnitus loudness, while NECK maneuvers induced a decrease of loudness.…”
Section: Comments On This Casesupporting
confidence: 92%
See 3 more Smart Citations
“…The identification of a somatic origin for her tinnitus thanks to the matching of self-reported history and modulation in the same somatic regions helped in addressing this patient to multidisciplinary somatic evaluation and treatment. Furthermore, the characteristics of tinnitus modulation found in this patient are consistent with what reported in the literature by some authors 32,33,41,42 . TMJ maneuvers induced an increase in tinnitus loudness, while NECK maneuvers induced a decrease of loudness.…”
Section: Comments On This Casesupporting
confidence: 92%
“…This case demonstrates that tinnitus modulation can be found even when no somatic disorder is present; in fact, somatic modulation of tinnitus is a widespread condition that can be present with or without underlying somatic disorders 31,40 . Furthermore, as previously discussed, several authors reported a large capability of somatic tinnitus modulation in multiple patient series ranging between 65.3% and 83.3% 32,35,[41][42][43]45,47,61,65 . In this patient, the negative history for self-reported somatic disorder suggests caution while taking into account a somatic origin for his tinnitus.…”
Section: Comments On This Casesupporting
confidence: 53%
See 2 more Smart Citations
“…Recent converging evidences suggest that the tinnitus-related neural activity is more complex and can be provoked or modulated by inputs from somatosensory, somatomotor and visual-motor system (Rocha and Sanchez, 2007;Sanchez et al, 2007;Sanchez and Rocha, 2011). Electroencephalographic (EEC) studies in tinnitus have highlighted several abnormalities regarding the background cerebral oscillations in various frequency bands, such as theta, delta, alpha, beta or gamma. Although previous EEC or magnetoencephalographic (MEG) studies on tinnitus sufferers reported conflicting data, a general tendency is a concentration of abnormalities mainly over the temporo-parietal (Shulman and Goldstein, 2002;Shulman et al, 2006;Schlee et al, 2009;Moazami-Goudarzi et al, 2010) and frontal regions (Shulman and Goldstein, 2002;Shulman et al, 2006).…”
Section: Introductionmentioning
confidence: 99%